Satisfacción al cliente en Consorcio Mega de la ciudad de Milagro - Carbo Castro, Mayra Rosario (2021)
This research work is focused on the research sub-line of the "Marketing and Commercialization" course of commerce, the objective of this case study is to know the degree of satisfaction of the clients of the Mega consortium of the city of Milagro, for which It is established to answer questions that will allow making the pertinent conclusions of the case. What factors affect the satisfaction of the Mega consortium customer? What is the perception that the customer has about the Mega consortium service? For this research, the qualitative methodology was taken as a basis, through a descriptive investigation, likewise the bibliographic, scientific and inductive methods were used; The information collection technique called a survey was used, for which a specific questionnaire was designed that was used with the clients of the Mega consortium, to know in a primary way the necessary information that allows to carry out the process of the proposed case study, all the predisposition of the administrator to carry out the investigation on this company.